Molecular Characterization of a Tetraspanin TSP11 Gene in Echinococcus granulosus and Evaluation Its Immunoprotection in Model Dogs - Xian, Jinwen; Zhao, Pengpeng; Wang, Ning; Wang, Weiye; Zhang, Yanyan; Meng, Jimeng; Ma, Xun; Wang, Zhengrong; Bo, Xinwen (Frontiers in Veterinary Science, 2021)
Cystic echinococcosis (CE) is a cosmopolitan zoonosis caused by the larval stage of Echinococcus granulosus, which affects humans and a wide range of mammalian intermediate hosts. Parasite tetraspanin proteins are crucial for host-parasite interactions, and therefore they may be useful for vaccine development or disease diagnosis. In the present study, the major antigen coding sequence of tetraspanin 11 (Eg-TSP11) from E. granulosus was determined. The results of immunolocalization showed that Eg-TSP11 was mainly located in the tegument of adult worms and protoscoleces. Western blotting analysis showed that the serum from dogs injected with recombinant EgTSP11 (rEg-TSP11) could recognize Eg-TSP11 among natural protoscolex proteins. Moreover, the serum from dogs with E. granulosus infection also recognized rEg-TSP11. Serum indirect enzyme-linked immunosorbent assays demonstrated that IgG levels gradually increased after the first immunization with rEg-TSP11 compared with those in the control group. Furthermore, the serum levels of interleukin 4, interleukin 5, and interferon gamma were significantly altered in the rEg-TSP11 group. Importantly, we found that vaccination with rEg-TSP11 significantly decreased worm burden and inhibited segment development in a dog model of E. granulosus infection. Based on these findings, we speculated that rEg-TSP11 might be a potential candidate vaccine antigen against E. granulosus infection in dogs.